Experimental flexural analysis of steel-fiber-reinforced concrete beams - Molina, Jonnathan; Naspud, Pilar; Nieto-Cárdenas, Xavier (ACI Avances en Ciencias e Ingenierías, 2026)
The use of steel fibers in concrete has been widely documented in numerous engineering applications due to the advantages they provide in terms of strength, crack control, and energy absorption capacity. However, in Ecuador, there is still limited knowledge among construction professionals regarding their structural properties and benefits. This research arises from the need to overcome the inherent limitations of conventional concrete, particularly in its post-elastic behavior and its response to cracking. This paper presents the results of an experimental study in which concrete mixtures with a nominal compressive strength of 24 MPa were designed, and the flexural behavior of four beam typologies was evaluated: plain concrete, steel fiber-reinforced concrete, conventional reinforced concrete, and concrete with a dual reinforcement system (steel fibers and reinforcing bars). Twelve specimens were tested under static loading following the procedure established in ASTM C1609. The results show that an appropriate combination of cement, aggregates, and a fiber dosage of 0.56 % by volume increases the ultimate flexural strength by 33.63 % in plain concrete beams and by 12.85 % in reinforced concrete beams. A significant improvement in ductility was also observed, with increases of 187.23 % in plain concrete beams and 38.02 % in reinforced concrete beams. The findings demonstrate the effectiveness of incorporating steel fibers in structural elements subjected to flexure, showing improvements at both mechanical and structural levels. The presence of fibers promotes a more uniform stress distribution, reduces tensile demands on longitudinal reinforcement, and enables more efficient utilization of reinforcing bars, resulting in increased load-carrying capacity for sections equivalent to those of conventional reinforced concrete. Additionally, enhanced energy absorption capacity and a significant reduction in crack width were confirmed.